Frost tolerance of various Pinus pure species and hybrids. Issue 3 (3rd July 2019) - Mabaso, Fanelesibonge; Ham, Hannél; Nel, André
Abstract : Pinus species are widely planted by the South African forestry industry and are utilised for pulp, paper and saw timber products. Historically, Pinus patula Schiede ex Schltdl. et Cham. was the most widely planted commercial species in the summer rainfall area, but has come under severe threat due to the fungus Fusarium circinatum . Fusarium circinatum causes mortality in nurseries and in-field after establishment. Other Pinus species, such as P. tecunumanii F.Schwerdtf. ex Eguiluz et J.P.Perry and P. oocarpa Schiede ex Schltdl., have been crossed with P. patula to increase tolerance to F. circinatum and these hybrids have largely overcome the post-planting mortality problem. However, these hybrid-partner species are more prone to frost damage. This study reviewed laboratory screening techniques to assess the frost tolerance level of a range of Pinus pure species and hybrids. In vitro screening was done with the electrolyte leakage and whole-plant freezing techniques. Seedlings and rooted cuttings from a range of genotypes, supplied by Sappi, were tested in vitro at different target temperatures (−3, −6, −9 and −12 °C) to determine their relative frost tolerance. These genotypes included a range of Pinus pure species, four interspecific hybrids ( P. patula × P. tecunumanii low elevation [LE], P. patula × P. tecunumanii high elevation [HE], P. elliottii Engelm. × P. caribaea Morelet), and a three-way cross ( P. patula × ( P. patula × P. oocarpa )). Results from this study indicated that the electrolyte leakage technique was a reliable method to determine frost tolerance under laboratory conditions, with similar pure species rankings as experienced under field conditions. The interspecific hybrids of P. patula × P. tecunumanii LE and HE ranked intermediate between the parental species and the P. patula × P. tecunumanii HE hybrid was more frost tolerant than the P. patula × P. tecunumanii LE hybrid.